An international exploration of barriers and tactics in the public sector innovation process. Issue 3 (4th March 2021) - Cinar, Emre; Trott, Paul; Simms, Christopher
ABSTRACT: This study deepens our knowledge on innovation barriers within public sector innovation (PSI) processes. Our research contributes to the barrier approach to innovation. We develop a conceptual framework, which expands the conventional view of barriers. The exploratory empirical evidence based on 99 cases from Italy, Japan and Turkey identifies the dynamic nature of the barriers within innovation processes. We uncover tactics that are used to overcome these barriers and the mechanisms that can surprisingly contribute to fruitful outcomes.